Perceptions of production related stakeholders towards Aarong and the Ayesha Abed foundation - Rahman, Rehnuma; Alim, Md. Abdul (BRAC, 2019)
Aarong and Ayesha Abed Foundation were established to support the artisans and rural women in Bangladesh. Thus, these production-related stakeholders are very · important for Aarong and AAF. This study was initiated to investigate the perception of the stakeholders about Aarong and AAF. Data were collected from production workers (PW), independent producers (IP) and employees of Aarong and AAF using a combination of qualitative and quantitative methods. Findings show that female staff of Aarong were relatively more dissatisfied compared to male, and half of the IPs working with Aarong were also dissatisfied. IPs and PWs expressed many grievances about Aarong and AAF but their willingness to stay connected with the organization was evident under these circumstances, it would be better for the organization to address these alarming issues immediately to run the business smoothly in future.